Relationship Of Facilities And Compensationt To Permata Sejahtera Bekasi Foundatio Employees Performance - Ari Widi Prakasa (PT. Publikasiku Academic Solution, 2023)
Research purposes; (1). To determine the effects of existing work facilities on the performance of foundation employees. (2). To determine the effects of employee compensation on the performance of foundation employees. (3). To determine the effects of work facilities and work compensation together on the performance of foundation employees. By using research methods, quantitative research approaches. In a process to find problems related to science using data in the form of mathematical and statistical numbers, as a means and tools to analyze the data collected as desired. Result: There is a significant effect between means and compensation on employee performance. There is a simultaneous influence of the means and compensation variables have a significant effect on employee performance. Means and compensation are proven to be able to partially mediate that can affect employee performance in the Permata Sejahtera Foundation Bekasi.